PS-B10-6: CAPILLARY-TO-ARTERIOLAR SIGNALLING, INFLAMMATION AND SMALL VESSEL DISEASE OF THE BRAIN. (January 2023) - Evans, Lowri Elizabeth; Taylor, Jade; Dabertrand, Fabrice; Pritchard, Harry; Schiessl, Ingo; Allan, Stuart; Greenstein, Adam
Abstract : Objective: Chronic cerebral inflammation is thought to be a mechanism by which hypertension causes small vessel disease of the brain, leading to dementia. Mouse studies have demonstrated enhanced small resistance artery constriction and neurovascular uncoupling in hypertension. We wished to examine whether acute exposure to the predominant inflammatory driver in hypertension, interleukin-1β; (IL-1β;) could account for this dual vascular deficit. Design and method: Pressure myography of freshly isolated mouse posterior cerebellar pial arteries was used to assess contributions of the inwardly rectifying K + 2.1 (KIR 2.1) channel to vasodilation. In order to assess neurovascular coupling from a vascular perspective, we adopted a recently described approach: the Capillary to Parenchymal Arteriole (CaPA) preparation. In the CaPA preparation, penetrating arterioles (< 40ums) with attached capillary branches are isolated and pressurised. The capillary branch and arteriole are independently stimulated via a micropipette and arteriole diameter is recorded. This approach enables the retrograde hyperpolarising signal from the KIR 2.1 channel, which propagates against the flow of blood in the brain, to be assessed both in terms of the extent of arteriole vasodilation and the speed of communication (video). In order to assess the effects of perivascular inflammation on cerebrovascular function, we incubated (in culture medium) small pial arteries with IL-1β; for 24 hours prior to study on a pressure myograph rig. KIR 2.1 function was assessed using 10 mM exogenous K + . Cerebral arterioles with attached capillaries were incubated with IL-1β; for 2 hours prior to CaPA study. We then examined the capillary-to-arteriolar signalling mechanism via application of 10 mM K + to the capillary. We also assessed arteriolar tone and reaction to directly applied K +, NS309 and U46619. Results: Preliminary data suggests that sub-acute incubation with exogenous IL-1β; had no effects on the degree of pressure induced constriction of either the pial artery or the arteriole. CaPA preparation showed that the KIR 2.1 capillary-to-arteriolar signalling was preserved as well as arteriolar responses to direct K +, NS309 and U46619 following IL-1β; exposure. Conclusions: Whilst chronic cerebral inflammation in the setting of hypertension results in cerebrovascular deficits, sub-acute exposure with IL-1β; does not appear to significantly impair cerebral microvascular function. Precisely how chronic exposure to inflammation in hypertension induces neurovascular uncoupling is the subject of ongoing investigation.